2008
DOI: 10.1590/s1415-47572008000300028
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sequence divergence rates in the 5 prime regulatory regions of young Drosophila melanogaster duplicate gene pairs

Abstract: While it remains a matter of some debate, rapid sequence evolution of the coding sequences of duplicate genes is characteristic for early phases past duplication, but long established duplicates generally evolve under constraint, much like the rest of the coding genome. As for coding sequences, it may be possible to infer evolutionary rate, selection, and constraint via contrasts between duplicate gene divergence in the 5 prime regions and in the corresponding synonymous site divergence in the coding regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…Indeed, it has been previously shown that there is a significant negative relationship between the expression correlation of duplicate genes and K a (Gu et al, 2002). Similar results have been obtained when analyzing duplicate genes in Arabidopsis thaliana, Drosophila melanogaster and humans (Ganko, Meyers and Vision, 2007;Kohn, 2008;Park and Makova, 2009). To-gether these results indicate that functional change of diverging duplicate genes at the coding sequence level is coupled with change in transcription factor binding sites and expression.…”
Section: We Began By Identifying Orfs and Promoter Regions From All Strainssupporting
confidence: 72%
“…Indeed, it has been previously shown that there is a significant negative relationship between the expression correlation of duplicate genes and K a (Gu et al, 2002). Similar results have been obtained when analyzing duplicate genes in Arabidopsis thaliana, Drosophila melanogaster and humans (Ganko, Meyers and Vision, 2007;Kohn, 2008;Park and Makova, 2009). To-gether these results indicate that functional change of diverging duplicate genes at the coding sequence level is coupled with change in transcription factor binding sites and expression.…”
Section: We Began By Identifying Orfs and Promoter Regions From All Strainssupporting
confidence: 72%
“…BLASTN implements a local alignment strategy whereas DIALIGN combines local alignment to seed subsequent global alignment. Both of these tools have previously been used in other CNS investigations ( 6 , 8 , 85 , 86 ). A case study using a known heat shock element ( 74 , 75 ) shows that both DIALIGN and BLASTN were successful in identifying the motif TTCnnGAA, with DIALIGN being more sensitive ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a selective advantage for spatially or temporally divided expression can produce highly conserved protein coding regions (a type of subfunctionalization) due to mutations in the enhancer regions [ 54 ]. Such changes in enhancer regions have been reported to occur in recent duplicates [ 55 ]. In some cases, novel function may come about with only a small level of sequence divergence of the protein coding region.…”
Section: Discussionmentioning
confidence: 99%